Effect of AZO film as seeding substrate on the electrodeposition and properties of Al-doped ZnO nanorod arrays. Issue 10 (December 2015) - Pruna, A.; Pullini, D.; Busquets, D.
Abstract: The fabrication of whole Al-doped ZnO nanostructured electrodes is reported by a two-step technology. Magnetron sputtered Al-doped ZnO (AZO) films were investigated as seeding substrates for the electrodeposition of Al-doped ZnO nanorod arrays. The nucleation, density, morphological and structural properties of Al-doped ZnO NRAs were analyzed as a function of precursor concentration and substrate and compared to undoped ZnO NRAs. High density and good crystal quality are reported for the Al-doped ZnO NRAs grown on AZO films from low precursor concentration.